161k views
4 votes
Simplify the expression where possible. (r^3)^ -2

User Umit Kaya
by
4.5k points

2 Answers

3 votes

Answer:

r^-6 OR 1 / (r^6)

Explanation:

For this expression, we can use exponential power rules to simplify.

Power to a power, you multiply the exponents.

So, (r^3)^-2 == r^-6

We can use the fact that negative exponents will be the base to the power in the denominator.

r^-6 == 1/(r^6)

Cheers.

User Harry Wood
by
4.9k points
3 votes

Answer:

Explanation:

We apply the properties of the power.


\left(r^3 \right)^(-2)=r^(3*(-2))=r^(-6)=(1)/(r^6)

User Bastan
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.